PELATIHAN PENGGUNAAN MENDELEY BAGI MAHASISWA ANGKATAN 2021 DAN 2022 JURUSAN PBSI, FKIP, UHO - Sumiman Udu; Fahruddin; Sri Suryana Dinar; Andi Muh. Ruum Sya'baan (PT. CASA CENDEKIA MEDIA, 2024)
This Community Service Program is entitled